Local Resources, Global Impact: Crafting Bioplastics from Salak and Cassava in Indonesia - Yesika, Benida; Al-jilani, Yazan; Balfour, Esmond Agurgo; Pwamang, Caroline Kachana (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The purpose of this study was to determine the effect of adding sorbitol and glycerol on the quality of bioplastics, as well as to determine the right formulation for making bioplastic starch from snake fruit and cassava seeds. Methodology: The method used was a Completely Randomized Design (CRD) with two factors, namely the addition of the first factor of sorbitol (1, 2, and 3 mL) and the second factor of glycerol addition (1, 2, and 3 mL), each experiment was repeated three times. The data obtained were analyzed using the analysis of variance test at a significant level of 0.05. Main Findings: The variation in sorbitol and glycerol addition significantly affects the characteristics of bioplastics, as confirmed by a One-Way ANOVA test (sig. < 0.05), indicating distinct differences based on the type and amount of plasticizer used. Optimal formulations for bioplastics made from salak seeds and cassava starch include: highest water resistance (96.19%) with 2 mL sorbitol, optimal thickness (0.33 mm) with 1 mL sorbitol, greatest tensile strength (68.93 kg/cm²) with 2 mL glycerol, and highest elongation (5.88%) with 3 mL glycerol. Novelty/Originality of this study: This study contributes to the advancement of bioplastic development by utilizing salak seed and cassava starch as novel base materials. The resulting bioplastics offer the potential to serve as environmentally friendly alternatives to conventional plastics, with the key advantage of being biodegradable. This innovation supports efforts to reduce synthetic plastic waste, which is notoriously difficult to decompose.